Activists of themselves: Liminality of Instagram and its role in the ethnic identity construction processes of third generation British Sikhs to their imagined identities. (June 2023) - Takhar, Amandeep; Bebek, Gaye; Jamal, Ahmad
Abstract: As a result of the rapid evolution of computer culture, social media and networking websites now provide the primary socialisation platforms for individuals across the world. With characteristics such as transcending time, space, and even cultures, these platforms impact individuals through increased interactions. Although past research shows how social media impacts on individuals' cultural affiliations and identity construction processes, research neglects to understand the role and impact of the characteristics of social media and networking environments as individuals engage in these virtual spaces. This paper uses Instagram as a case study, to demonstrate the liminal nature of social media spaces and looks at how this virtual space and its characteristics evoke a sense of reflexivity with regards to identity construction amongst young British Sikhs in the U.K. We highlight how the empowering characteristics of this virtual space impact their identity and just how the communities that are formed by individuals through Instagram, act as a further acculturative agent, as they attempt to deal with the tensions that they experience as a result of being both British and Sikh. Findings implicate how brands can engage with and support the individuals going through this reflective identity re/construction process. Highlights: Social media creates a third space that is everywhere but nowhere. Liminality of online world encourages individuals to explore identities. Online communities are influential whilst exploring self. Online communities present lucrative spaces for brands to reach out. Social media presents a potential space for marketers to reach out to online consumers.